2019
DOI: 10.1080/10640266.2019.1586219
|View full text |Cite
|
Sign up to set email alerts
|

Family involvement in eating disorder treatment among Latinas

Abstract: Latinos are less likely to seek health care for eating disorders and more likely to drop out of treatment than members of other ethnic groups, highlighting existing challenges to engagement in traditional mental health care. This study explored the role of family in the treatment of adult Latinas with eating disorders through content analysis of family sessions adjunctive to cognitive behavioral therapy. This study yielded insight into the experiences of 10 Latinas with eating disorders (M age = 39.90 years) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
0
19
0
3
Order By: Relevance
“…Other Level 2 studies identified by the scoping review that, whilst not conceptually original, offered transferable findings included: general family education and support (Gisladottir et al, 2017; Gísladóttir & Svavarsdóttir, 2011), integrated approaches to treatment of adults that combine medical, nutritional and psychological treatment with family sessions (Onnis et al, 2012; Reyes‐Rodríguez et al, 2013; Reyes‐Rodríguez et al, 2019), brief strategic family therapy (Doba et al, 2013), a parental counseling intervention derived from brief Adlerian psychodynamic psychotherapy (Amianto et al, 2014), a relational/motivational adaptation of the multifamily therapy group model (Tantillo et al, 2015), and a couple‐based intervention for binge‐eating disorder integrated with cognitive‐behavioral therapy principles (Runfola et al, 2018). This range of progressive development demonstrates the variety of approaches and varying intensity of current FIT options for adults affected by EDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other Level 2 studies identified by the scoping review that, whilst not conceptually original, offered transferable findings included: general family education and support (Gisladottir et al, 2017; Gísladóttir & Svavarsdóttir, 2011), integrated approaches to treatment of adults that combine medical, nutritional and psychological treatment with family sessions (Onnis et al, 2012; Reyes‐Rodríguez et al, 2013; Reyes‐Rodríguez et al, 2019), brief strategic family therapy (Doba et al, 2013), a parental counseling intervention derived from brief Adlerian psychodynamic psychotherapy (Amianto et al, 2014), a relational/motivational adaptation of the multifamily therapy group model (Tantillo et al, 2015), and a couple‐based intervention for binge‐eating disorder integrated with cognitive‐behavioral therapy principles (Runfola et al, 2018). This range of progressive development demonstrates the variety of approaches and varying intensity of current FIT options for adults affected by EDs.…”
Section: Resultsmentioning
confidence: 99%
“…Offering additional context, key issues of importance in implementation and direction for clinical practice can be extrapolated. A recent example of this was, in order to investigate the role of family in the treatment of adult Latina patients with binge EDs, sessions with relatives adapted from the UNiting couples in the Treatment of Eating disorders‐BED edition (UNITE‐BED) model were offered aside CBT (Reyes‐Rodríguez et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Existing empirically supported treatments for EDs do not explicitly discuss discrimination (Pennesi & Wade, 2016). Although researchers have begun to modify cognitive behavioral therapy to address culture specific factors for Latine individuals (e.g., Reyes‐Rodríguez et al, 2019; Shea et al, 2012), no treatment has been modified to address discrimination specifically. Treatments that effectively provide coping strategies to manage discriminatory experiences and reduce binge eating could improve both effectiveness of treatment and retention rates by more adequately addressing the unique experiences and realities of being Latine.…”
Section: Discussionmentioning
confidence: 99%
“…Die existierenden Berichte verwendeten teilweise lediglich Fragebögen ohne direkte Interviews der Beteiligten, fokussierten ausschließlich auf bestimmte Diagnosen, z. B. Essstörungen, oder bezogen entweder Patienten zusammen mit Bezugspersonen oder Behandlern ein, nicht jedoch alle 3 Gruppen [19][20][21]. Daher war das Ziel dieser Studie alle Interessensgruppen in einer repräsentativen Befragung mittels semi-strukturierter, direkter Interviews in unterschiedlichen Behandlungssettings (Tageskliniken, offene und geschützte stationäre Bereiche) zu untersuchen, um dadurch ein besseres Verständnis für das Ausmaß der aktuellen Einbeziehung von Bezugspersonen, die Erwartungen und Wünsche aller Interessensgruppen und die tatsächlich thematisierten Inhalte zu gewinnen.…”
Section: Conclusion Whether Caregivers Were Contacted and Involvedunclassified